Dynamic Mechanism of High Quality Development of National Fitness Public Service: An Analysis Based on Interpretative Structural Model - Deng, Liang; Yang, ZongQian; Shi, LiZhen; Huang, XiaoLing (Quality in Sport, 2024)
National Fitness Public Service is integral to people’s livelihoods and connects with public sentiment. Promoting the high-quality development of National Fitness Public Service is not only a necessary response to the overall high-quality development of China’s economy and society but also an essential measure to meet the public’s expectations for a high-quality life. The "14th Five-Year Plan" period represents a new journey in the construction of National Fitness Public Service in China and a critical period for establishing a high-quality development and high-quality life paradigm. Under these new circumstances, it is crucial to clarify the driving forces behind the high-quality development of National Fitness Public Service. This clarification is significant for local governments to advance National Fitness Public Service and enhance service levels.This study, based on the Interpretive Structural Modeling (ISM), systematically constructs the driving mechanism of high-quality development for National Fitness Public Service. The final model is structured as "1-3-9-19," where "1" represents the goal layer, "3" the superficial direct driving factors, "9" the intermediate driving factors, and "19" the foundational driving factors. This model aids in strengthening the theoretical understanding of the high-quality development of National Fitness Public Service and provides theoretical support for local governments in formulating regional policies.